(untitled) (Bangladesh Agronomy Journal, 2024)
The experiment was conducted at Jute Agriculture Experimental Station (JAES), Manikganj; JRRS, Rangpur and JRSS, Jashore to determine the optimum sowing date of jute var. BJRI Tossa Pat-8. The experiment was laid-out in RCBD with three replications and variety O-9897 used as control. Crops were sown on five different dates i.e., 20 March, 30 March, 10 April, 20 April and 30 April regarded as treatment. Crops were attained recommended cultural practices and harvested at 120 days after sowing. The results showed that BJRI Tossa Pat-8 (Robi-1) sown on 10 April to 20 April gave significantly higher fibre and stick yields at Manikganj (3.37 t ha−1 and 6.33 t ha−1 respectively); Rangpur (3.11 t ha−1 and 5.22 t ha−1, respectively) and Jashore (3.96 t ha−1 and 5.57 t ha−1, respectively) with an average 14% higher than control. Bangladesh Agron. J. 2024, 26(2): 27-33